Introduction to reactive gas dynamics - Brun, R. (Raymond), 1932- (Oxford : Oxford University Press, 2009)
Many actual technological problems require the knowledge of the physical and chemical phenomena and processes taking place in high energy gas flows. This book presents an introductory analysis, theoretical and experimental, of these media highlighting both their fundamental characteristics and applied aspects.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Relaxation (Gas dynamics); Gas dynamics; Nonequilibrium statistical mechanics